Microstructural characterization, solidification characteristics and tensile properties of Al–15%Mg2Si–x(Gd–Sb) in-situ composite - Hamidreza Ghandvar; Mohd Hasbullah Idris; Tuty Asma Abu Bakar; Afshin Nafari; Norhayati Ahmad (Journal of Materials Research and Technology, 2020)
In the present study, complex modification of primary and eutectic Mg2Si particles in Al–15%Mg2Si, composite was examined by simultaneous addition of gadolinium (Gd) and antimony (Sb). It was realized that combined addition of 1.5 wt. % Gd–Sb was efficient for modifying Mg2Si, in which coarse dendritic primary Mg2Si particles were changed into a perfect truncated octahedral morphology with a decrease in average size from 40 µm to 12 µm, an increase in density of Mg2Si per area from 495 to 1435 particle/mm2, and a reduction in the aspect ratio from 1.34 to 1.17. Furthermore, eutectic Mg2Si particles transformed from plate-like to fiber-like structure with an average eutectic Mg2Si cell decreasing from 132 µm to 51.22 µm. Thermal analysis revealed that nucleation and growth temperatures of primary Mg2Si increased with addition of Gd–Sb. However, it had an opposite effect for eutectic Mg2Si. It was proposed that refinement/modification of primary Mg2Si particles was mainly derived from formation of Mg3Sb2 compounds as heterogeneous nuclei for primary Mg2Si. Meanwhile, the preferred growth of primary Mg2Si crystals along <100> direction can be obviously suppressed by the absorption and poisoning of Gd and Sb. The tensile results presented that addition of 1.5 wt. % Gd–Sb to the composite enhanced the UTS and %El from 204.79 MPa and 2.65% in base condition to 242.73 MPa and 3.9% in the modified composite, respectively. This study demonstrated that combined addition of Gd–Sb can provide a better effect on the modification and tensile properties of Al–15%Mg2Si composite than addition of Gd or Sb separately.